Effectiveness and Mechanisms of Low-Intensity Pulsed Ultrasound on Osseointegration of Dental Implants and Biological Functions of Bone Marrow Mesenchymal Stem Cells - Chao Liang; Xiu Liu; Yuwei Yan; Rongxin Sun; Jun Li; Wei Geng (Hindawi Limited, 2022)
Dental implant restoration is the preferred choice for patients with dentition defects or edentulous patients, and obtaining stable osseointegration is the determining factor for successful implant healing. The risk of implant failure during the healing stage is still an urgent problem in clinical practice due to differences in bone quality at different implant sites and the impact of some systemic diseases on bone tissue metabolism. Low-intensity pulsed ultrasound (LIPUS) is a noninvasive physical intervention method widely recognized in the treatment of bone fracture and joint damage repair. Moreover, many studies indicated that LIPUS could effectively promote the osseointegration of dental implants and improve the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). This review is aimed at investigating the research progress on the use of LIPUS in dental implant medicine from three aspects: (1) discuss the promoting effects of LIPUS on osseointegration and peri-implant bone regeneration, (2) summarize the effects and associated mechanisms of LIPUS on the biological functions of BMSCs, and (3) introduce the application and prospects of LIPUS in the clinical work of dental implantation. Although many challenges need to be overcome in the future, LIPUS is bound to be an efficient and convenient therapeutic method to improve the dental implantation success rate and expand clinical implant indications.